INCREASED COMPETITIVENESS OF CONSTRUCTION ENTERPRISES ON THE BASIS OF ORGANISATIONAL-ECONOMIC DECISIONS OF PERSONNEL POTENTIAL MANAGEMENT - J. R. Emirbekova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The development of an algorithm for optimising the formation and use of human resources of a construction enterprise.Methods. The research basis consists in a generalised methodology  for personnel management, as well as specific methods for logical  and statistical analysis of management decision-making in  construction activities. The approaches, criteria, indicators and methods for assessing the effectiveness of human resource  management are studied alongside factors influencing the efficiency  resource potential management in a construction enterprise.Results. A quantitative methodology for the selection of qualified  staff for the implementation of construction projects is proposed.  The indicators of the effectiveness of the staff potential are  determined. Qualitative and quantitative data for the optimal  personnel formation for the construction project realisation are  systematised. An algorithm for optimising the personnel potential of  a construction enterprise is proposed. The use of this algorithm will  inform the choice of organisational and economic solutions for the  formation and effective use of qualified personnel at the expense of  combining professions, thereby reducing the cost and duration of construction work and increasing the resource efficiency and competitiveness of the construction enterprise.Conclusion. The labour potential of a construction enterprise can  significantly contribute to increased efficiency if it is used  appropriately and in an organised manner, using modern scientific  methods of management. Methods for building and organising the  activity of the personnel management system are proposed and a  mechanism for establishing relationships between the employer and employees that promote the most effective use of all types of resources for the development of the enterprise according to  strategic objectives is disclosed. The dominant role of the personnel  component of the resource potential of the construction enterprise issubstantiated, having its management provided by organisational and economic decisions on the selection and placement of personnel  in order to organise the rhythmic and high-quality work of each site and the entire construction site as a whole.